Moisture Absorption Speed of Textiles for Personal Care Use to Develop Reusable Products - Bettina Mehne; Elisabeth Eppinger; Lilia Sabantina (Engineering Proceedings, 2024)
Quick moisture absorbency is a requirement of textiles for a wide range of applications, such as sports and work wear, medical and personal care use, agricultural applications, and seating furniture. On the textile level, the absorbency speed depends on the fiber, yarn, and fabric properties and structures, as well as multi-layer combinations. Accordingly, the technical development of these textile products includes selecting appropriate combinations of textile structures. This study presents the absorption speed of different fabric structures. The conclusions on the interaction of porosity and liquid transfer provide guidance for developing and selecting textiles with absorbency requirements.